Logistics Distribution Route Design Using Taboo Search Method - Nugraha, Yaskie Cahyana Septiviandra Ade; Donoriyanto, Dwi Sukma; Nugraha, Isna (Journal La Multiapp, 2025)
Logistics, as the science and art of managing goods, energy, information, and other resources, plays a vital role in the economy through shipping, receiving, warehousing, and distribution. Optimal routes can reduce travel distances and maximize transport capacity, optimize resource use, and reduce the environmental impact of logistics activities. PT Spectrum Indo Transport is a logistics company serving the Java-Bali region with 40 trucks, including wingbox, colt diesel, and colt diesel long. However, the company often experiences delays in delivery. The largest demand is for 275 gram cereals distributed to the East Java region. The East Java region includes Malang (3,100 kg), Mojokerto (2,500 kg), Gresik (2,500 kg), Lamongan (2,300 kg), Nganjuk (2,700 kg), and Surabaya (2,300 kg). The fleet chosen is a colt diesel with a capacity of 5 tons due to high consumer demand. The company wants to optimize the distance of the delivery route to prevent delays in the distribution of goods. The purpose of this study is to improve the efficiency of the delivery of the Colt Diesel Box fleet in East Java carried out by PT Spectrum Indo Transport through the application of the Tabu Search method in determining the distribution route. It is expected that by implementing Tabu Search, the company can achieve more efficient delivery. With the shortest route, it will provide an optimal influence on the delivery of goods and can meet delivery on time.